Risk assessment in gas and oil pipelines based on the fuzzy Bow-tie technique - P. Heyrani; A. Baghaei (بهداشت و ایمنی کار, 2016)
Introduction: Nowadays, gas and oil account for 60 percent of world energy resources. Transporting crude oil and its products are accomplished through a number of ways among which pipelines are of the utmost significance. Considering the extent of pipelines in installation and residential areas and also high potential for damage, the safety of these pipes and application of risk management principles have undeniable importance. Bow-tie risk assessment method is one of the ways to determine safety level. The tool is a qualitative and semi-quantitative method the data of which are implemented by specialists and experts via conducting surveys.